2013
DOI: 10.1128/genomea.00520-13
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Five Multilocus Sequence Types of Nonencapsulated Streptococcus pneumoniae

Abstract: Nonencapsulated Streptococcus pneumoniae can colonize the human nasopharynx and cause conjunctivitis and otitis media. Different deletions in the capsular polysaccharide biosynthesis locus and different multilocus sequence types have been described for nonencapsulated strains. Draft genome sequences were generated to provide insight into the genomic diversity of these strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…During nasopharyngeal carriage, other functions of PspC have been indicated by previous reports showing its importance in adherence (16,17,(20)(21)(22)(23)40). In addition, our observation that PspC binding of factor H by unencapsulated strains had no effect on complement resistance may help in understanding the loss of PspC in naturally occurring unencapsulated S. pneumoniae strains (41,42). Other gene products in the naturally occurring unencapsulated strains, such as the PspC-like protein PspK, were shown to play a role in colonization and adherence but did not bind factor H (43)(44)(45).…”
Section: Discussionsupporting
confidence: 64%
“…During nasopharyngeal carriage, other functions of PspC have been indicated by previous reports showing its importance in adherence (16,17,(20)(21)(22)(23)40). In addition, our observation that PspC binding of factor H by unencapsulated strains had no effect on complement resistance may help in understanding the loss of PspC in naturally occurring unencapsulated S. pneumoniae strains (41,42). Other gene products in the naturally occurring unencapsulated strains, such as the PspC-like protein PspK, were shown to play a role in colonization and adherence but did not bind factor H (43)(44)(45).…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, recent studies have revealed that a subset of non‐encapsulated isolates form a distinct phyletic group basal to other pneumococcal strains (Croucher et al ., ; Valentino et al ., ). Thus, we added isolates from this group, ending up with 32 pneumococcal genomes (Antic et al , unpublished) (Keller et al ., ) (light blue, Supporting Information Table S1). Finally, for the MAST, we added seven genomes from isolates from eye infections and non‐encapsulated strains that are distributed throughout the phylogenetic tree (Antic et al ., under review).…”
Section: Methodsmentioning
confidence: 99%
“…This included all unencapsulated nasopharyngeal genomes in Croucher et al . 19 (16 genomes) and 8 draft genomes of nasopharyngeal isolates currently available from either the NCBI GenBank or European Nucleotide Archive (ENA), including 5 genomes newly deposited to NCBI GenBank 70 . When available, we maximized the diversity of this set by downloading several representatives, spanning various dates of isolation, or when additional information on strain diversity was available (e.g.…”
Section: Methodsmentioning
confidence: 99%